The Antarctic Treaty : 20th anniversary. - Benson, Lucy Wilson.; United States. Department of State. Office of Public Communication. Editorial Division. (Washington, D.C. : U.S. Dept. of State, Bureau of Public Affairs, Office of Public Communication, Editorial Division, 1979)
"October 1979"--P. [2] Caption title. Mode of access: Internet.